Parkinsonian Syndromes in Motor Neuron Disease: A Clinical Study - Pasquini, Jacopo; Trogu, Francesca; Morelli, Claudia; Poletti, Barbara; Girotti, Floriano; Peverelli, Silvia; Brusati, Alberto; Ratti, Antonia; Ciammola, Andrea; Silani, Vincenzo; Ticozzi, Nicola (Frontiers in Aging Neuroscience, 2022)
Background. Parkinsonian syndromes may rarely occur in motor neuron disease (MND). However, previous studies are heterogeneous and mostly case reports or small case series. Therefore, we aimed to identify and characterize patients with concurrent parkinsonian syndromes extracted from a cohort of 1042 consecutive cases diagnosed with MND at a tertiary Italian Center. Methods. Diagnosis of Parkinson’s disease (PD), progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS) was made according to current criteria. Clinical characterization included: upper and lower motor neuron disease features, typical and atypical parkinsonian features, oculomotor disorders, cognitive testing, MRI features, and, when available molecular neuroimaging. Genetic testing was carried out for major MND and PD-associated genes. Results. Parkinsonian syndromes were diagnosed in 18/1042 (1.7%) of MND patients (7 PD, 6 PSP, 3 CBS, 2 other parkinsonisms). Based on phenotype, patients could be categorized into amyotrophic lateral sclerosis (ALS)-parkinsonism and primary lateral sclerosis (PLS)-parkinsonism clusters. Across the whole database, parkinsonism was significantly more common in PLS than in other MND phenotypes (12.1% vs 1.1%, p=5.0x10-10). MND patients with parkinsonian features had older age of onset, higher frequency of oculomotor disorders, cognitive impairment, and family history of parkinsonism or dementia. Two patients showed pathogenic mutations in TARDBP and C9orf72 genes. Conclusion. Specific patterns in MND-parkinsonism were observed, with PLS patients often showing atypical parkinsonian syndromes and ALS patients more frequently showing typical PD. Systematic clinical, genetic, and neuropathologic characterization may provide a better understanding of these phenotypes.